Institutionalising the ‘skollie’: social labelling and philanthropic institutional reform at Klaasjagersberg State Institution for Coloured boys c. 1934-1979 - Barnard, Daniela (Stellenbosch : Stellenbosch University, 2022)
Thesis (MA)--Stellenbosch University, 2022.